Study on Antioxidant Potential and Nutrition Status of Different Underutilized Fruits in South Gujarat - B. B., Abuj; Karmakar, N.; P. R., Vododariya; A. V, Narwade,; S, Tripathi (International Journal of Bio-resource and Stress Management, 2017)
A survey experiment was carried out at in department of Soil Science and Agricultural Chemistry, N. M. College of Agriculture during 2015−2016 to determine antioxidant and biochemical potentials in some underutilized fruit crops of South Gujarat region. The experiment was undertaken in above mentioned minor fruits, which were collected from local cultivar of South Gujarat includes the districts of Navsari, Surat, Bharuch, Valsad, Tapi, Narmada and Dang. Amongst all the analyzed fruits, Emblica officinalis L. fruits was found to possess highest antioxidant content (31.35%) followed by Artocarpus heterophyllus L. (25.18%) and Zizyphus mauritiana L. (15.46%), Tamarindus indica L. (8.50%). The antioxidant contents viz., ascorbic acid63.57 mg 100 g-1, total phenol 31.06 GAE 100 g-1, antioxidant enzymes like catalase (CAT) 33.38 U g-l fresh weight, superoxide dismutase (SOD) 2.98 U g-1 fresh weight and peroxidase (POD) 9.79 U g-1 fresh weight and antioxidant activity 74.18 μg.ml-1 was reported higher in Emblica officinalis L. fruits collected Navsari, Pardi and Gandevi grown fruits of South Gujarat. Maximum content of biochemical parameters was obtained in Tamarindus indica L. (13.7071%) fruits followed by Zizyphus mauritiana L. (12.52%) and Artocarpus heterophyllus L. (8.127%) fruits. The Biochemical contents viz., Total soluble solid (TSS) 40.07 oBrix, Total fat 0.61 g 100 g-1, total carotenoids 22.00 µg 100 g-1, reducing sugar 18.09 g 100 g-1, soluble sugar 19.79 g 100 g-1, protein 3.02 g 100 g-1 and acidity 12.17 was reported higher in Tamarindus indica L. collected from different places of South Gujarat. The consumption of these fruits as food supplements, their cultivation, conservation by the native tribal farming community should be encouraged in south Gujarat region.